SEARCHING FOR SOLUTIONS TO STUDENT SPEECH PROBLEMS - Mirzaeva Ziyoda Madjiddinovna (Bright Mind Publishing, 2025)
In this article, an attempt was made to study the active words used in the speech of readers in content, and it is evident in our examples that many of these words are foreign words. The article was followed by solutions to these problems.
Keywords: Education, reader, word, speech, problem, scientist, technique, social network.